TILL-D: An Aegilops tauschii TILLING Resource for Wheat Improvement - Rawat, Nidhi; Schoen, Adam; Singh, Lovepreet; Mahlandt, Alexander; Wilson, Duane L.; Liu, Sanzhen; Lin, Guifang; Gill, Bikram S.; Tiwari, Vijay K. (Frontiers in Plant Science, 2018)
Aegilops tauschii (2n=2x=14, genome DD), also known as Tausch’s goatgrass, is the D genome donor of bread or hexaploid wheat Triticum aestivum (2n=2x= 42, AABBDD genome). It is a rich reservoir of useful genes for biotic and abiotic stress tolerance for wheat improvement. We developed a TILLING (Targeting Induced Local Lesions In Genomes) resource for Ae. tauschii for discovery and validation of useful genes in the D genome of wheat. The population, referred to as TILL-D, was developed with ethyl methanesulphonate (EMS) mutagen. The survival rate in M1 generation was 73%, out of which 22% plants were sterile. In the M2 generation 25% of the planted seeds showed phenotypic mutations such as albinos, chlorinas, no germination, variegated, sterile and partially fertile events, and 2,656 produced fertile M2 plants. The waxy gene was used to calculate the mutation frequency (1/70 kb) of the developed population, which was found to be higher than known mutation frequencies for diploid plants (1/89 kb- 1/1000 kb), but lower than that for a polyploid species (1/24 kb- 1/51 kb). The TILL-D resource, together with the newly published Ae. tauschii reference genome sequence, will facilitate gene discoveries and validations of agronomically important traits and their eventual fine transfer in bread wheat.